Diagnosis of the interplanetary magnetic field azimutal component by means of the Antarctic magnetic observatory - Yu. P. Sumaruk (Ukrainian Antarctic Journal, 2008)
Methods of the diagnosis of the interplanetary magnetic field azimutal component by means of the Antarctic magnetic observatory Vostok data are proposed. Comparation of the calculated and observed data show satisfactory results.